PENGARUH RETURN ON ASSETS DAN DEBT TO EQUITY RATIO TERHADAP DIVIDEND PAYOUT RATIO DI PERUSAHAAN TERCATAT DI BURSA EFEK INDONESIA PERIODE 2016-2018 - Eka Meiliya Dona (Ekonomika, 2020)
The objectiveistodetermineifthere wasa significant effectof return on assetsandthe ratio of debt-to-equity ratio ofthe partialpayment ofdividendsandsimultaneously. Based ondata analysisanddiscussion, it can be concludedthatthere isinfluence ofReturn On AssetandDebt ToEquityRatio ofDividenPayout Ratio. Based on the resultsof dataprocessingresults obtainedfrom theReturn OnAsset(X1) to the dividendpayout ratio(Y), fort-count lessthant-table is (-0.011) <t-table (2.11) means that Hois acceptedandof Harejected. So it provedthatreturn on assetdoes notaffect thedividendpayout ratio. whileDebt ToEquityRatio(X2) onthe dividendpayout ratio(Y), fort-count lessthant-table is (-3.098) <t-table (2.11) means that Hois acceptedandof Harejected. So it provedthatdebt to equityratio does notaffect thedividendpayout ratio. As for theF test(simultaneous) 4829is greaterthanthe Ftable3.68thatthereis significant relationship betweenreturn on assetanddebt-to-equity ratio todividendpayout ratio. The percentagecontribution ofreturn on assetanddebt-to-equity ratio todividendpayout ratio of0392or(39.2%), while the rest of60.8% influencedorexplainedbyother variables notincluded in the modelisstudyis the ratio ofliquidity, solvency ratio, the ratio ofgrowthandrateof return(cashmere, 2008:106).